Comparative Effectiveness of mRNA and Inactivated Whole-Virus Vaccines Against Coronavirus Disease 2019 Infection and Severe Disease in Singapore . (6th June 2022) - Premikha, M; Chiew, Calvin J; Wei, Wycliffe E; Leo, Yee Sin; Ong, Benjamin; Lye, David Chien; Lee, Vernon J; Tan, Kelvin Bryan
Abstract: Compared with individuals vaccinated with Pfizer-BioNTech/Comirnaty, recipients of Sinovac-CoronaVac and Sinopharm were 2.37 (95% CI, 2.29–2.46) and 1.62 (95% CI, 1.43–1.85) times more likely to be infected with coronavirus disease 19, respectively, while individuals vaccinated with Moderna were 0.42 (95% CI, 0.25–0.70) times less likely to develop severe disease.